Burashev Y.D., Sultankulova K.T., Strochkov V.M., Sansyzbay A.R., Sandybayev N.T., Orynbayev M.B. Phylogenetic analysis of surface HA gene, of equine inﬂuenza A/equine/LKZ/09/2012 (H3N8) virus strains: Research Institute for Biological Safety Problems» Zhambulskaya oblast, Korday region, Gvardeyskyi (Eurasian Journal of Ecology, 2018)
This paper presents the results of epizootological monitoring of equine influenza in the Republic ofKazakhstan, which were organized the expeditions to South Kazakhstan, Zhambyl, Almaty, East Kazakhstan, Kostanai, Aktobe and West Kazakhstan regions. For laboratory investigations in different regions ofthe Republic of Kazakhstan, 2404 samples were collected and delivered to RIBSP. The outbreak of equineinfluenza virus (EIV) in Kazakhstan was confirmed by isolating the virus in chick embryos, sequencing thesurface hemagglutinin HA gene, and then analyzing the resulting nucleotide sequence at the BLAST base.All investigated samples were taken from un-vaccinated horses with expressed clinical signs of respiratorydisease in 2007 and 2012 in southern and northern Kazakhstan. EIV H3N8 was isolated in chicken eggsfrom 30 nasal swabs from horses with acute respiratory disease, which were tested positive by DirectigenFlu A. Isolation was confirmed by haemagglutination assay and RT-PCR assay of the M, HA and NA gene.HA sequences of the Kazakhstan isolates appeared to be more closely related to viruses isolated in early2000 in Asia. These results suggested that viruses with fewer changes than those on the main evolutionarylineage may continue to circulate. On the other hand, analysis of deduced NA amino acid sequences weremore closely related to viruses isolated in outbreaks in Europe and Asia during 2003-2007. Phylogeneticanalysis characterized the Kazakhstan EIV isolates as a member of the Eurasian lineage by the haemagglutinin (HA) protein alignment, but appeared to be a member of the Florida sublineage clade 2 by theneuraminidase (NA) protein sequence suggesting that reassortment might be a possible explanation. Thetopology of the maximum-likehood tree for both HA and NA sequences showed four clades correspondingto the Pre-diverge, American, Eurasian and Florida lineage viruses. The Kazakhstan isolates were well supported within the Eurasian clade, as seen for the HA protein with bootstrap value 90% and 99% within theFlorida sublineage clade II for the HA protein. Our findings suggest that the Kazakhstan strains representan example of “evolution” and probably reassortment between genetically distinct co-circulated strains.Key words: virus, equine influenza, PCR, sequencing, phylogenetic analysis.